After-ripening induced transcriptional changes of hormonal genes in wheat seeds: the cases of brassinosteroids, ethylene, cytokinin and salicylic acid. - Vijaya R Chitnis; Feng Gao; Zhen Yao; Mark C Jordan; Seokhoon Park; Belay T Ayele (PLoS ONE, 2014)
Maintenance and release of seed dormancy is regulated by plant hormones; their levels and seed sensitivity being the critical factors. This study reports transcriptional regulation of brassinosteroids (BR), ethylene (ET), cytokinin (CK) and salicylic acid (SA) related wheat genes by after-ripening, a period of dry storage that decays dormancy. Changes in the expression of hormonal genes due to seed after-ripening did not occur in the anhydrobiotic state but rather in the hydrated state. After-ripening induced dormancy decay appears to be associated with imbibition mediated increase in the synthesis and signalling of BR, via transcriptional activation of de-etiolated2, dwarf4 and brassinosteroid signaling kinase, and repression of brassinosteroid insensitive 2. Our analysis is also suggestive of the significance of increased ET production, as reflected by enhanced transcription of 1-aminocyclopropane-1-carboxylic acid oxidase in after-ripened seeds, and tight regulation of seed response to ET in regulating dormancy decay. Differential transcriptions of lonely guy, zeatin O-glucosyltransferases and cytokinin oxidases, and pseudo-response regulator between dormant and after-ripened seeds implicate CK in the regulation of seed dormancy in wheat. Our analysis also reflects the association of dormancy decay in wheat with seed SA level and NPR independent SA signaling that appear to be regulated transcriptionally by phenylalanine ammonia lyase, and whirly and suppressor of npr1 inducible1 genes, respectively. Co-expression clustering of the hormonal genes implies the significance of synergistic and antagonistic interaction between the different plant hormones in regulating wheat seed dormancy. These results contribute to further our understanding of the molecular features controlling seed dormancy in wheat.